Implementasi SAK ETAP Dalam Penyusunan Laporan Keuangan Pada Usaha Kecil Menengah (UKM) - Yuniar, Tiara; Epi, Yus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Financial reports are needed by companies to evaluate business activities and performance, provide financial information, determine the value of a company and make decisions by stakeholders. The main source in preparing financial reports is Financial Accounting Standards (SAK) which are prepared by a competent and independent body. SAK is a procedure or rule that must be adhered to in preparing financial reports, so that financial reports occur. Apart from SAK, there are other financial reporting standards. One of them is the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). The problem that often occurs is that SMEs are not yet able to make financial reports. Financial reports are very important for predicting financial flows in Small and Medium Enterprises. SME Financial Reports. This research aims to prepare financial reports for Berkah Boutique Business in accordance with the Financial Accounting Standards for Non-Accountable Entities. This research uses a quantitative descriptive method. Primary data sources are in the form of interviews, observations and transaction evidence. The results of this research show the financial reports of Berkah Boutique Business in the form of a balance sheet financial position report, profit and loss report, report on changes in capital (equity).